Differences in the Effectiveness of Autogenic and Supportive Therapy for Post Traumatic Stress Disorder (PTSD) in the Elderly Post-Flood in Kanorejo Village, Rengel District, Tuban Regency - Hanim Nur Faizah; Hyan Oktodia Basuki (Alliance oh Health Activists (AloHA), 2021)
PTSD (Post Traumatic Syndrome Disorder) is a syndrome of anxiety, autonomic lability, and experiencing flashbacks of very sad experiences after physical and emotional stress that exceeds the endurance limits of ordinary people. In addition, PTSD can also be defined as an extreme physically and mentally debilitating condition that occurs after a person sees, hears, or experiences a severe traumatic event and or an event that threatens his life. This research belongs to the type of experimental analytical research with a quasi-experimental design with a prospective approach. This study used probability sampling technique and tested with Wilcoxon test and logistic regression. Wilcoxon test results obtained p value 0.000